A Conceptualization Framework of Allyship: Bidirectional Allyship Between Black Heterosexual Women and White Gay Males. (October 2021) - Scaramuzzo, Peter; Bartone, Michael D.; Young, Jemimah L.
Allyship is a complicated idea laden with multiple, layered assumptions. One should not presume that allyship conceptually permeates all social justice movements. One should not presume that allyships develop to combat or dismantle a predefined socially constructed ism. A critical interrogation of allyship and allyship constructions necessitates recognition of broader, universal tenets of allyships anywhere. This must go further to embrace the nuanced, situated, dynamic, critically problematic, and complex dimensions rooted in individual lived experiences intersecting multiple marginalizations which contribute as praxis toward an actualizing of individual allyships. Although we will blur constructed distinctions as we progress, here, we endeavor to surface and deliberate upon the derivations and functions and shapes of allyships between two demographic categories, made arbitrarily distinct here for the purposes of engaging in discursive analysis: cisgender heterosexual Black women and cisgender gay White men. In short, we are proposing a way to view this allyship as bidirectional allyships, grounded in social justice frames of existing: a way to see each respective group as traveling within their own lane down a collectively traveled highway. Each traverses the space along their own course, traveling down "their own road."